The Effect of Gadget Usage on the Social Development of Children Aged 3-5 Years: Literature Review - Setiani, Diah (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The gadget is a term in English which defines a small electronic device with various functions. The use of gadgets has both positive and negative impacts. This study uses a Systematic Literature Review, a synthesis of systemic, precise, comprehensive literature studies by identifying, analyzing, evaluating through collecting existing data with an explicit search method and involving a critical review process in selecting the studies. The data used by 7 national journals were obtained from the results of screening several journals from Google Scholar and the National Library of Indonesia. Based on the results of the journals collected and the author’s analysis, it was found that there was a significant influence between the use of gadgets on the social development of children aged 3-5 years. For further researchers, it is hoped that they can research with two different groups, namely the control group that uses and does not use gadgets.